Association of Social Media and Desire Result in Examination with Study Time of Students - Khan, Zahid; Hussain, Jawad; Yaseen, Asadullah (Pakistan Languages and Humanities Review, 2023)
Academic achievement is one of the major goals of students which depends on many factors. The crucial factor is study time of students. The students study more get higher grad in examination. The present study aims to assess the effects of factors on student’s study time which is measure by number of study hours at home/hostel or university. The population of this study is undergraduate students of University of Malakand. Ninety students from various faculties are selected by stratified random sampling method. The academic faculties are considered as strata. A structure questionnaire is formatted and distributed among students. The data is presented by tables. Multiple linear regression model is used to identify the significant factors associated with number of study hours of students. Use of social media and desire result of the students are found significantly associated with response variable. Assumption of the regression model is tested, and found satisfactory.